Strategi Bauran Pemasaran 7ps dan Social Media Engagement Dalam Live Streaming Commerce: Studi Kasus Tiga Brand Umkm Kategori Fashion Di Tiktok Shop - Destria, Chelma; Bella, Eka; Pamungkas, Envira (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
Given the rising trend of Live Streaming Commerce (LSC) on social media today, this study analyzes the marketing strategies of three Indonesian fashion SMEs brands, namely Tenue de Attire, Rurik.id, and 3SECOND, which market their products on TikTok Shop. Employing a qualitative content analysis method, this research evaluates the implementation of the 7Ps of Marketing Mix concept (Product, Price, Place, Promotion, Physical Evidence, People, Process) and the theory of Social Media Engagement, focusing on hosts credibility and interaction during live sessions. The findings indicate that Rurik.id and 3SECOND are more effective in applying the 7Ps strategies and gaining viewers’ engagement compared to Tenue de Attire. Factors such as dynamic interactions, diverse product offerings, competitive pricing, and hosts’ credibility play a significant role in increasing viewer attention and purchase intention. This study concludes that the success of live streaming commerce lies on the effective integration of marketing strategies and digital communication methods, particularly on social media. It is expected to provide valuable insights for Indonesian SMEs in optimizing sales through digital platforms, especially TikTok Shop. Keywords: Live Streaming Commerce, 7Ps Marketing Mix, Social Media Engagement, TikTok Shop.